CMET-20. EVIDENCE OF CNS RESPONSE OF PEMBROLIZUMAB FOR LEPTOMENINGEAL CARCINOMATOSIS AT A SINGLE CELL RESOLUTION. (5th November 2018) - Alvarez-Breckenridge, Christopher; Prakadan, Sanjay; Lee, Eudocia; Tolaney, Sara; Nayak, Lakshmi; Lin, Nancy; Bihun, Ivanna; Chukwueke, Ugonma; Oh, Kevin; White, Michael; Gerstner, Elizabeth; Lawrence, Donald; et al.
Abstract: Approximately 8% of patients with cancer develop leptomeningeal carcinomatosis (LMD). LMD is associated with approximately 4 week median survival and a paucity of treatment options beyond palliative shunting. We performed a phase II study of the PD-1 inhibitor pembrolizumab in LMD from any solid tumor malignancy (NCT02886585). The primary endpoint is the rate of overall survival at 3 months (OS3). A Simon two-stage design was used to compare a null hypothesis OS3 of 18% against an alternative of 43%. Serial CSF, blood samples and tumor samples were collected to elucidate the genomic and transcriptional determinants of response to immunotherapy in central nervous system lesions. A total of 18 patients were accrued and the median follow-up of patients still alive was 6.8 months (range: 2.2 to 7.6 months). At the time of data retrieval, 11 patients (61%) were alive at three months after enrollment (OS3). Therefore, the study met its primary endpoint. Whole exome sequencing of tissue samples and cell-free DNA from CSF and blood, as well as single-cell RNA sequencing of CSF, were carried out to decipher tumor evolution, track immune cell recruitment, and identify biomarkers of response. Analysis of 7877 tumor and immune cells across 6 patients demonstrated patient-specific tumor clustering and evidence of T cell and antigen presenting cells recruited to the CSF following pembrolizumab treatment. Longitudinal CSF samples demonstrated genetic and transcriptomic differences in tumor and immune cells suggesting response to treatment in patients that reached OS3 compared with those that did not. These findings suggest that pembrolizumab has activity in LMD and that CSF provides an opportunity to monitor the clonal evolution of the tumor and immune microenvironment in LMD.